Search for time-dependent CP violation in D0 → K+ K- and D0 → π+ π- decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2021)
A search for time-dependent violation of the charge-parity symmetry in D0→K+K− and D0→π+π− decays is performed at the LHCb experiment using proton-proton collision data recorded from 2015 to 2018 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 6 fb−1. The D0 meson is required to originate from a D∗(2010)+→D0π+ decay, such that its flavor at production is identified by the charge of the accompanying pion. The slope of the time-dependent asymmetry of the decay rates of D0 and ¯D0 mesons into the final states under consideration is measured to be ΔYK+K−=(−2.3±1.5±0.3)×10−4, ΔYπ+π−=(−4.0±2.8±0.4)×10−4, where the first uncertainties are statistical and the second are systematic. These results are compatible with the conservation of the charge-parity symmetry at the level of 2 standard deviations and improve the precision by nearly a factor of 2.